Resolution on the results of scientific-practical conference "Clinical evidence of increasing overall survival in the treatment of metastatic breast cancer", held on 29 November 2014 under the auspices of the Department of health of Moscow - E. T. Bairamov; A. V. Belonogov; V. V. Brusnichkina; A. V. Bulakh; M. Y. Byahov; S. N. Gurov; G. G. Eremeev; N. V. Zhukov; L. G. Zhukova; L. M. Kogonia; P. V. Koposov; L. K. Ovchinnikova; et al. (Исследования и практика в медицине)
Objectives: discussion of modern treatment options for metastatic breast cancer (MBC), the determining of the optimal treatment for subgroups of patients with poor prognosis.